2021
DOI: 10.1186/s12936-021-03718-x
|View full text |Cite|
|
Sign up to set email alerts
|

Climate-proofing a malaria eradication strategy

Abstract: Two recent initiatives, the World Health Organization (WHO) Strategic Advisory Group on Malaria Eradication and the Lancet Commission on Malaria Eradication, have assessed the feasibility of achieving global malaria eradication and proposed strategies to achieve it. Both reports rely on a climate-driven model of malaria transmission to conclude that long-term trends in climate will assist eradication efforts overall and, consequently, neither prioritize strategies to manage the effects of climate variability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 76 publications
0
24
0
Order By: Relevance
“…In this context, few studies suggest that climate change has a major impact on changes in vector borne diseases, specifically, changes on malaria transmission in different parts of the world 24 , 25 , Sarkar et al 26 , 27 . Climate change has a direct influence on malaria transmission and an increase in the temperature and rainfall is more conducive for the breeding of mosquito and cause the increase in frequency and intensity of the malaria diseases 28 – 31 .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, few studies suggest that climate change has a major impact on changes in vector borne diseases, specifically, changes on malaria transmission in different parts of the world 24 , 25 , Sarkar et al 26 , 27 . Climate change has a direct influence on malaria transmission and an increase in the temperature and rainfall is more conducive for the breeding of mosquito and cause the increase in frequency and intensity of the malaria diseases 28 – 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, climate variations favoring higher temperatures may exacerbate vector-transmitted diseases such as malaria and other parasites, as these are expected to proliferate better with higher temperatures [ 167 , 168 , 169 ]. A recent review examining climate change in relation to malaria indicated that, while considerable evidence shows that warmer conditions tend to facilitate malaria transmission, the relationship between rainfall and malaria may be nonlinear [ 170 ]. For instance, while the time between rainfall episodes can foster the rapid growth of mosquito populations, longer spacing between rainfall episodes can restrict the growth rate of mosquito populations.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…1186/ s12936-021-03718-x. *Correspondence: h.nissan@lse.ac.uk 1 Grantham Research Institute for Climate Change and the Environment, London School of Economics and Political Science, London, UK Full list of author information is available at the end of the article…”
Section: Publisher's Notementioning
confidence: 99%
“…Following publication of the original article [1], it was brought to our attention that the entries under the section 'Practical recommendations' had not been numbered, when they should have been numbered as follows:…”
mentioning
confidence: 99%